A three-dimensional porous graphene / iron oxide electromagnetic shielding composite film and a preparation method thereof
By combining graphene oxide with nano-iron tetroxide, a three-dimensional porous electromagnetic shielding material is constructed, which solves the problems of poor dispersion and industrialization of existing graphene electromagnetic materials, and achieves high-efficiency electromagnetic wave absorption and reflection performance, making it suitable for multi-purpose electromagnetic shielding products.
Patent Information
- Application Number
- CN202411686112.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-11-24
AI Technical Summary
Existing graphene electromagnetic shielding materials suffer from problems such as high filler content, poor dispersibility, and easy agglomeration, making it difficult to form an efficient conductive mesh. Furthermore, existing preparation methods are not environmentally friendly and are costly.
Three-dimensional graphene/iron oxide composite materials were prepared by self-assembly method. Microscopic heterogeneous interfaces were constructed by reducing and self-assembling graphene oxide. Combined with heat treatment process, the electromagnetic shielding performance was optimized.
A high-performance, lightweight, flexible, and electromagnetically shielding graphene-based composite material has been developed, which is suitable for industrial production, reduces costs, and improves dispersibility and conductivity.
Smart Images

Figure CN119463667B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, specifically, it relates to a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film and its preparation method. Background Technology
[0002] With the rapid development of electronic equipment and communication technologies and their widespread application in military, medical, industrial, and commercial fields, electromagnetic radiation pollution has become increasingly serious, ranking as the fourth largest environmental hazard after noise pollution, air pollution, and water pollution. Electromagnetic radiation can affect the normal operation of electronic equipment and human health. To reduce or eliminate the negative impacts of electromagnetic radiation, high-performance electromagnetic interference (EMI) shielding materials have attracted considerable attention.
[0003] The preparation of efficient, broadband, lightweight, and flexible electromagnetic shielding materials using graphene-based materials has broad prospects. Existing graphene electromagnetic shielding materials mostly use graphene as a filler in polymer polymerization to form electromagnetic shielding materials. However, filled materials suffer from drawbacks such as high filler content and poor dispersibility. Furthermore, the strong van der Waals forces and electrostatic interactions within graphene sheets make it difficult for them to interact with polymers, and excessive graphene tends to agglomerate, making it difficult to maximize the formation of a conductive mesh. Summary of the Invention
[0004] The purpose of this invention is to provide a method for successfully synthesizing three-dimensional graphene / iron tetroxide (3D rGO / Fe3O4) composite electromagnetic shielding material by means of self-assembly. The purpose of this invention is also to provide a high-performance electromagnetic shielding film coated with 3D rGO / Fe3O4 slurry that is environmentally friendly and suitable for industrial production.
[0005] This invention uses graphene oxide and nano-ferric oxide as raw materials to prepare porous 3DrGO / Fe3O4 composite materials, improving the dispersibility of nano-ferric oxide. The composite material is further modified by heat treatment to enhance its electromagnetic shielding performance. A uniformly sized Fe3O4 nanosphere aqueous dispersion is prepared using a dispersant-assisted method, and a microscopic graphene oxide-nano-Fe3O4 heterostructure is constructed using graphene oxide reduction self-assembly, obtaining a "sphere (Fe3O4)-network (3DrGO)" structure. By constructing the ferric oxide nanosphere-three-dimensional graphene heterostructure and employing appropriate heat treatment processes, the electromagnetic wave shielding and absorption performance of the 3DrGO / Fe3O4 composite electromagnetic shielding material is improved, thereby achieving the goal of preparing high-performance graphene composite electromagnetic shielding materials.
[0006] To address the aforementioned technical problems, the present invention employs the following technical solution:
[0007] The purpose of this invention is to provide a method for preparing a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film, comprising the following steps:
[0008] Step 1: Disperse graphene oxide in deionized water using ultrasound to open up the graphene oxide sheets and obtain a graphene oxide solution.
[0009] Step 2: Disperse nano-Fe3O4 into deionized water using ultrasonication to obtain a Fe3O4 dispersion.
[0010] Step 3: Add the dispersant in batches, ensuring each batch is evenly dispersed. After complete dispersion, continue sonicating for a certain period of time to obtain a mixed solution.
[0011] Step 4: Sonicate the graphene oxide solution obtained in Step 1 for a certain time, and then add the mixed solution obtained in Step 3 under strong stirring conditions, and then sonicate for a certain time.
[0012] Step 4 involves combining nano-Fe3O4 particles with graphene oxide.
[0013] Step 5: Then add ascorbic acid, seal, perform hydrothermal reduction, cool to room temperature after the reaction is complete, soak in water multiple times, crush, filter and wash at least three times, spread evenly and freeze dry to obtain 3D rGO / Fe3O4 composite material.
[0014] Step 6: Heat-treat the 3D rGO / Fe3O4 composite material under inert gas protection, then mix it with polyvinylpyrrolidone and dry grind it to obtain powder.
[0015] After heat treatment, the graphite layered structure of reduced graphene oxide is more fully reduced, oxygen-containing functional groups are decomposed in large quantities, lattice defects are greatly eliminated, and the structure is more complete; the time and temperature of heat treatment are controlled.
[0016] Step 7: Add water-based polyurethane to the powder in batches. After the addition is complete, continue stirring for a certain period of time, then coat it onto copper foil or other types of substrates such as PET, PI, and conductive cloth, and dry it to obtain the composite film.
[0017] Furthermore, in step 1, the concentration of the graphene oxide solution is 1 mg / mL to 10 mg / mL; the ultrasonic frequency is 300 W to 1000 W; and the ultrasonic time is 2 h to 5 h.
[0018] Furthermore, in step 2, the concentration of the iron oxide dispersion is between 0.5 mg / mL and 5 mg / mL; the ultrasonic frequency is between 300 W and 1000 W; and the time is between 2 h and 5 h.
[0019] Furthermore, in step 3, the dispersant is hydroxymethyl cellulose, and the amount of dispersant used is 0.5% to 5%.
[0020] Furthermore, the stirring speed for strong stirring is 1000 rpm to 2500 rpm.
[0021] Furthermore, in step 5, hydrothermal reduction is performed at 60℃~100℃ for 1h~3.5h; the freeze-drying is carried out in a vacuum freeze-drying oven with the temperature controlled at -10℃~-50℃ for 50h~82h.
[0022] Furthermore, in step 6, the inert gas is argon, and the heat treatment is carried out at 500℃~1000℃ for 1.5h~5h in a tube furnace.
[0023] Furthermore, in step 7, the mass ratio of solid to liquid is 1:(6-15).
[0024] Furthermore, in step 7, the product is dried at 40℃~110℃ for 2h~8h in a vacuum drying oven.
[0025] Further, in step 7, a coating is applied using a coater, with a coating thickness of 30μm-400μm.
[0026] A three-dimensional porous graphene / iron oxide electromagnetic shielding composite membrane prepared by any of the above methods.
[0027] The crystal lattice of Fe3O4 particles is a complex face-centered cubic structure (composed of oxygen atoms). 3+ Occupying the tetrahedral interstitial space (site A), Fe 2+ and Fe 3+ Together they occupy the octahedral interstices (B sites). In this invention, Fe... 2+ and Fe 3+Through the superexchange interaction of oxygen ions, Fe3O4 particles also possess ferrimagnetism. This invention improves the absorption loss and multiple reflection performance of graphene through structural regulation. This invention modifies graphene and optimizes processes to effectively improve dispersibility and conductivity, thereby reducing costs and improving shielding effectiveness. This invention designs a novel graphene composite material based on structuring and composite methods. First, a three-dimensional graphene (3D rGO) network is successfully and safely prepared by reducing graphene oxide using a solvothermal reduction method. The three-dimensional structure further improves the problem of graphene's tendency to agglomerate while maintaining the good conductivity of two-dimensional materials. Then, a three-dimensional porous 3D rGO / Fe3O4 composite material is successfully prepared through self-assembly. The three-dimensional porous structure reduces the density of the composite material on the one hand, and on the other hand, ensures that electromagnetic waves can penetrate into the material's interior. The internal pores synergistically enhance the impedance mismatch at the interface between the material bulk and free space. In addition, through process optimization, a scientific and efficient large-scale, customized preparation process is summarized, which is environmentally friendly and suitable for industrial production.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] This invention utilizes a combination of graphene oxide reduction and self-assembly, self-assembled nanoparticles, steam reduction, and tube furnace heat treatment to prepare a three-dimensional porous graphene / ferric oxide (3D rGO / Fe3O4) composite electromagnetic shielding coating. Its advantages include readily available and inexpensive raw materials, a safe and simple preparation process. During the reduction of graphene oxide, the surface epoxy functional groups and hydroxyl groups are gradually removed, and the continuously enhanced van der Waals forces and π-π stacking interactions increase the number of crosslinks between graphene particles, thereby generating a three-dimensional graphene (3D rGO) network. Fe3O4 nanospheres are uniformly dispersed in deionized water using a dispersant-assisted method, and then constructed with graphene oxide using a liquid-phase co-reduction method to form a microscopic heterogeneous interface "sphere (Fe3O4)-network (3D rGO)" structure. By optimizing the coating formulation and application process of the 3D rGO / Fe3O4 composite electromagnetic shielding material, the overall performance of the electromagnetic shielding product is improved. This achieves the goal of developing multi-purpose, high-performance electromagnetic shielding products.
[0030] The preparation process of this invention is simple and easy to control, the raw materials are inexpensive and readily available, and it is environmentally friendly; it can prepare lightweight, high-strength, stable, flexible, and highly electromagnetically shielding graphene-based composite electromagnetic shielding materials on demand.
[0031] To further understand the features and technical content of this invention, please refer to the following detailed description and accompanying drawings. However, the accompanying drawings are for reference and illustration only and are not intended to limit the invention. Attached Figure Description
[0032] Figure 1 Photograph of the three-dimensional graphene / iron tetroxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of this invention;
[0033] Figure 2 A photograph of the bent three-dimensional graphene / iron tetroxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of this invention;
[0034] Figure 3 Infrared spectral comparison diagram of Embodiment 1 of the present invention;
[0035] Figure 4 Comparison spectrum of electromagnetic shielding effectiveness in Embodiment 1 of the present invention;
[0036] Figure 5 Microscopic morphology and elemental distribution diagram under a scanning electron microscope in Embodiment 1 of the present invention. Detailed Implementation
[0037] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, while not limiting the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0038] Example 1: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this example is achieved through the following steps:
[0039] Step 1: Under an ultrasonic frequency of 600W, 0.95g of graphene oxide was uniformly dispersed in 400mL of deionized water to obtain a graphene oxide solution.
[0040] Step 2: Under an ultrasonic frequency of 600W, 0.05g of nano-Fe3O4 is uniformly dispersed in 100mL of deionized water to obtain a Fe3O4 dispersion.
[0041] Step 3: Disperse 0.0025g HMC into the surface of the iron oxide dispersion in three small, uniform portions. After complete dispersion, continue sonication for 30 minutes to obtain a mixed solution.
[0042] Step 4: Sonicate the graphene oxide solution obtained in Step 1 (ultrasonic frequency of 600w) for 60min, under strong stirring (stirring speed of 2000rpm), then add the mixed solution, and then sonicate for 30min under the condition of (ultrasonic frequency of 600w).
[0043] Step 5: Then add 0.9g of ascorbic acid (VC), seal with plastic wrap, heat to 95℃, and hydrothermally reduce for 2 hours under the heat. After the reaction is complete, cool to room temperature, change the water and soak several times, crush every other day, filter and wash three times, spread evenly in a glass dish, and place in a vacuum freeze dryer. Freeze dry at -40℃ for 72 hours to obtain 3D rGO / Fe3O4 composite material.
[0044] Step 6: Press the freeze-dried powder as compactly as possible into a ceramic boat, place it in a tube furnace, and heat-treat it for 3 hours under an argon atmosphere at 800°C.
[0045] Step 7: Take 1g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05g of polyvinylpyrrolidone K30 (PVP), and dry grind it in a mortar for 40min. Put the ground powder into a 100mL beaker, take 9g of waterborne polyurethane, and add it to the beaker in three portions of 5g, 2g, and 2g at 5min, 10min, and 15min respectively under stirring conditions. Continue stirring for 300min, coat it on copper foil with a coater, and dry it in a drying oven for 1h. After it is completely dry, cut it into 4cm×4cm sample pieces.
[0046] A photograph of the three-dimensional graphene / iron tetroxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of this invention is shown below. Figure 1 As shown.
[0047] A photograph of the bent three-dimensional graphene / iron tetroxide (3D rGO / Fe3O4) composite electromagnetic shielding coating film of Example 1 of this invention is shown below. Figure 2 As shown.
[0048] The infrared spectrum comparison diagram after heat treatment in Example 1 of the present invention is shown below. Figure 3 As shown, by Figure 3 It can be seen that the heat-treated sample is at 3750cm. -1 The significant decrease in the characteristic peak is due to the breakage of the OH chemical bonds at high temperatures, resulting in the release of gas. At 1360 cm⁻¹ -1 The COC characteristic peaks at the point were also significantly weakened. Infrared spectroscopy indicates that the oxygen-containing functional groups remaining after heat treatment were further reduced, graphene defects in the sample were reduced, and the structure was more complete.
[0049] The electromagnetic shielding effectiveness comparison spectrum after heat treatment in Example 1 of this invention is shown below. Figure 4 As shown. By Figure 4 The results of the electromagnetic shielding effectiveness test in the X-band are shown. The test frequency was 8.2 GHz to 12.4 GHz, and the test sample size was 40 mm × 40 mm. As can be seen from the figure, the average electromagnetic shielding effectiveness (SET) reached over 70 dB.
[0050] The SEM image of Embodiment 1 of the present invention is as follows: Figure 5 As shown, (a) is a 3DrGO sample, and (b) is a 3DrGO / Fe3O4 microporous structure. From... Figure 5 As can be seen, the three-dimensional graphene has a regular morphology, and the proportion of nano-Fe3O4 is relatively small, with no agglomeration observed. The nano-Fe3O4 is uniformly dispersed on the surface and in the gaps between the assembled graphene sheets. This indicates that the 3D rGO and Fe3O4 composite effect is good, and the macroscopic state of the powder particles is also improved.
[0051] Example 2: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this example is achieved through the following steps:
[0052] Step 1: Under an ultrasonic frequency of 600W, 0.4g of graphene oxide was uniformly dispersed in 350mL of deionized water to obtain a graphene oxide solution.
[0053] Step 2: Under an ultrasonic frequency of 600W, 0.1g of nano-Fe3O4 is uniformly dispersed in 150mL of deionized water to obtain a Fe3O4 dispersion.
[0054] Step 3: Disperse 0.005g of HMC into the surface of the iron oxide dispersion in three small, uniform portions. After complete dispersion, continue sonication for 30 minutes to obtain a mixed solution.
[0055] Step 4: Sonicate the graphene oxide solution obtained in Step 1 (ultrasonic frequency of 600w) for 60min, under strong stirring (stirring speed of 2000rpm), then add the mixed solution, and then sonicate for 30min under the condition of (ultrasonic frequency of 600w).
[0056] Step 5: Then add 0.9g of ascorbic acid (VC), seal with plastic wrap, heat to 95℃, and hydrothermally reduce for 2 hours under the heat. After the reaction is complete, cool to room temperature, change the water and soak several times, crush every other day, filter and wash three times, spread evenly in a glass dish, and place in a vacuum freeze dryer. Freeze dry at -40℃ for 72 hours to obtain 3D rGO / Fe3O4 composite material.
[0057] Step 6: Press the freeze-dried powder as compactly as possible into a ceramic boat, place it in a tube furnace, and heat-treat it for 3 hours under an argon atmosphere at 800°C.
[0058] Step 7: Take 1g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05g of polyvinylpyrrolidone K30 (PVP), and dry grind it in a mortar for 40min. Put the ground powder into a 100mL beaker, take 9g of waterborne polyurethane, and add it to the beaker in three portions of 5g, 2g, and 2g at 5min, 10min, and 15min respectively under stirring conditions. Continue stirring for 300min, coat it on copper foil with a coater, and dry it in a drying oven for 1h. After it is completely dry, cut it into 4cm×4cm sample pieces.
[0059] Tests showed that the average magnetic shielding effectiveness (SET) reached 77 dB.
[0060] Example 3: The preparation method of the three-dimensional porous graphene / iron oxide electromagnetic shielding composite film in this example is achieved through the following steps:
[0061] Step 1: Under ultrasonic conditions (ultrasonic frequency of 600w), 0.9g of graphene oxide is uniformly dispersed in 350mL of deionized water to obtain a graphene oxide solution.
[0062] Step 2: Under ultrasonic conditions (ultrasonic frequency of 600w), 0.1g of nano-Fe3O4 is uniformly dispersed in 150mL of deionized water to obtain Fe3O4 dispersion.
[0063] Step 3: Disperse 0.005g of hydroxymethyl cellulose (HMC) evenly onto the surface of the iron oxide dispersion in three small portions. After complete dispersion, continue sonication for 30 minutes to obtain a mixed solution.
[0064] Step 4: Sonicate the graphene oxide solution obtained in Step 1 (ultrasonic frequency of 600w) for 60min, under strong stirring (stirring speed of 2000rpm), then add the mixed solution, and then sonicate for 30min under the condition of (ultrasonic frequency of 600w).
[0065] Step 5: Then add 0.9g of ascorbic acid (VC), seal with plastic wrap, heat to 95℃, and hydrothermally reduce for 2 hours under the heat. After the reaction is complete, cool to room temperature, change the water and soak several times, crush every other day, filter and wash three times, spread evenly in a glass dish, and place in a vacuum freeze dryer. Freeze dry at -40℃ for 72 hours to obtain 3D rGO / Fe3O4 composite material.
[0066] Step 6: Press the freeze-dried powder as compactly as possible into a ceramic boat, place it in a tube furnace, and heat-treat it for 3 hours under an argon atmosphere at 800°C.
[0067] Step 7: Take 1g of the 3D rGO / Fe3O4 composite material after heat treatment in step 6, mix it with 0.05g of polyvinylpyrrolidone K30 (PVP), and dry grind it in a mortar for 40min. Put the ground powder into a 100mL beaker, take 9g of waterborne polyurethane, and add it to the beaker in three portions of 5g, 2g, and 2g at 5min, 10min, and 15min respectively under stirring conditions. Continue stirring for 300min, coat it on copper foil with a coater, and dry it in a drying oven for 1h. After it is completely dry, cut it into 4cm×4cm sample pieces.
[0068] Tests showed that the average magnetic shielding effectiveness (SET) reached 77 dB.
Claims
1. A method for preparing a three-dimensional porous graphene / iron oxide electromagnetic shielding composite film, characterized in that, The preparation method includes the following steps: Step 1: Disperse graphene oxide in deionized water using ultrasound to obtain a graphene oxide solution; Step 2: Disperse nano-Fe3O4 into deionized water using ultrasonication to obtain a Fe3O4 dispersion. Step 3: Add dispersant to the iron oxide dispersion in batches, ensuring each batch is evenly dispersed. After complete dispersion, continue sonication for a certain period of time to obtain a mixed solution. Step 4: Sonicate the graphene oxide solution obtained in Step 1 for a certain time under strong stirring conditions, then add the mixed solution, and sonicate again for a certain time. Step 5: Then add ascorbic acid, seal, perform hydrothermal reduction, cool to room temperature after the reaction is complete, soak in water multiple times, crush, filter and wash at least three times, spread evenly and freeze dry to obtain 3D rGO / Fe3O4 composite material. Step 6: Heat-treat the 3D rGO / Fe3O4 composite material under inert gas protection, then mix it with polyvinylpyrrolidone and dry grind it to obtain powder. The inert gas is argon, and the heat treatment is carried out at 500℃~1000℃ for 1.5h~5h. Step 7: Add water-based polyurethane to the powder in batches. After the addition is complete, continue stirring for a certain period of time, then coat it onto copper foil or PET, PI, or conductive cloth substrates, and dry it to obtain the composite film.
2. The preparation method according to claim 1, characterized in that, In step 1, the concentration of the graphene oxide solution is 1 mg / mL to 10 mg / mL; the ultrasonic frequency is 300 W to 1000 W; and the ultrasonic time is 2 h to 5 h.
3. The preparation method according to claim 1, characterized in that, In step 2, the concentration of the iron oxide dispersion is between 0.5 mg / mL and 5 mg / mL; the ultrasonic frequency is 300 W to 1000 W, and the time is between 2 h and 5 h.
4. The preparation method according to claim 1, characterized in that, In step 3, the dispersant is hydroxymethyl cellulose, and the amount of dispersant used is 0.5% to 5%.
5. The preparation method according to claim 1, characterized in that, The stirring speed for strong stirring is 1000-2500 rpm.
6. The preparation method according to claim 1, characterized in that, In step 5, hydrothermal reduction is carried out at 60℃~100℃ for 1h~3.5h; the freeze drying is carried out in a vacuum freeze drying oven, with the temperature controlled at -10℃~-50℃ for 50h~82h.
7. The preparation method according to claim 1, characterized in that, In step 7, the mass ratio of solid to liquid is 1:(6-15).
8. The preparation method according to claim 1, characterized in that, In step 7, the coating thickness is 30μm-400μm, and it is dried at 40℃-110℃ for 2h-8h.
9. A three-dimensional porous graphene / iron oxide electromagnetic shielding composite membrane prepared by any one of claims 1-8.
Citation Information
Patent Citations
Graphene-loaded nanometer Fe3O4 / aqueous polyurethane composite magnetic conductive wave absorbing coating material and preparation method thereof
CN104962185A
Graphene / ferroferric oxide composite material and preparation method and application thereof
CN110678055A
